Stress levels, sense of coherence and coping strategies among students at a South African University - Matumba, Fungai (My University, 2020)
Background: University education is crucial to the South African economy since it empowers students with skills, knowledge and attitudes for the world of work. Students with a manageable level of stress are ready to face academic challenges and mostly succeed in their studies. An estimated 80% of university students worldwide were reported to have experienced academic stress at some point during their studies, due to a variety of university demands. Research has indicated that there is a high prevalence of stress among university students, and that medical students are more stressed than nonmedical students. Continuous and excessive stress has a potential impact on the students’ health, mental state and academic performance. Universities need to be aware of factors such as the students’ Sense of Coherence (SOC) and their choice of coping strategies which determine stress levels, since it is crucial in the designing of intervention strategies. SOC was hypothesised to moderate the relationship between stress and the four components of stress coping strategies: Active Emotional Coping (AEC), Passive Emotional Coping (PEC), Active Problem Coping (APC) and Passive Problem Coping (PPC). Objectives: The objective of this study was to examine the relationships among stress, Sense of Coherence and coping strategies. It also aimed at comparing stress levels among medical and non-medical students. Methodology: A non-experimental, correlational, between subjects and cross-sectional survey design was used with a sample (N=366) of students, at a selected South African University. The total sample consisted of 286 females (78.7%) and 77 males (21%) and 2 others (0.3%) who refused to disclose their gender status. Stress was measured by the Perceived Stress Scale, Sense of Coherence by the Orientation to Life Scale, and Coping Strategies by the Stress Coping Inventory. The Statistical Package for Social Sciences (SPSS) version 25 was used to conduct Pearson Correlations, Confirmatory Factor Analysis, T-tests, Moderated Regression Analysis and Frequencies. Results: Results showed that there were no statistically significant differences in the stress levels of medical and psychology students. Female students reported significantly higher stress levels than male students. Single students reported significantly higher stress levels than married students. Students with children reported significantly higher stress levels than those without children. Perceived stress had a negative statistically significant relationship with SOC, AEC and APC but had a statistically positive relationship with PEC and PPC. A positive, statistically significant relationship was found between SOC and active coping strategies. SOC also had a negative statistically significant relationship with passive coping strategies. Results also showed that SOC moderated the relationship between Perceived stress and all the components of stress coping, except for AEC. Conclusions: Perceived stress, SOC and components of stress coping affect the mental health of students, this in turn affects their academic performance. SOC influences the type of coping strategies students adopt to deal with stressful academic events. The type of coping strategies a student adopts determines their stress levels. Universities need to design stress reduction interventions, strengthen the students’ SOC and assist them in choosing active coping strategies that can reduce their stress levels
A research project in partial fulfilment of the requirements for the degree of MA by Coursework and Research in the field of Social and Psychological Research in the Humanities, University of Witwatersrand, 2020